Poetic devices analysis: The effect of rhyming words on creating mood in Adi Kusrianto’s poem “Beautiful Mourn” - Mar’atussolekhah, Aulia (Maliki Interdisciplinary Journal, 2023)
Rhyme is one of great poetic devices for a poet to express their emotions and experiences. The way rhyme is used in a poem can transmit certain moods to the readers. Therefore, this study aimed to described the effect of rhyming words on creating mood in Adi Kusrianto’s poem “Beautiful Mourn” based on Attridge (1995) theory. It employed descriptive-qualitative methodology and the data were collected in the form of words. The study results found there are six different words included turned, dead, head, thorns, storm, and mourns in two stanzas that provided a starting point for understanding the role of rhyme in shaping the aesthetic and emotional qualities of “Beautiful Mourn”. The carefully selected words and their placement in the rhyme scheme helped establish a specific mood successfully. The researcher found that through the rhyming words used within the poem, “Beautiful Mourn” is a charming piece of art that skilfully weaves the themes of sorrow and beauty, creating a mood of sad, mourning, and weeping in a harmony.